Community Advocate Model: Linking Communities, School Districts, and Universities to Support Families and Exchange Knowledge - Mary D. Burbank; Rosemarie Hunter (The University of Alabama, 2022)
Increasingly diverse communities that reach across traditional boundaries are on the rise in urban communities in the United States. Changes taking place within these communities also affect K-16 institutions that serve them. As the landscape of American neighborhoods evolves, stakeholders collaborate to forge partnerships and programs that value and reflect these changes. The Community Advocate Model (CAM) presents a unique opportunity for establishing reciprocal relationships between parents from historically underserved populations and K-16 educators. By connecting families, school, community resources, and the university, parents are able to exchange information and have direct access to system educators. Similarly, rapidly increasing immigrant populations enhance these neighborhoods and systems with rich and diverse language and cultures, bringing new opportunities and challenges for local schools and higher education to meet their academic needs. Our research indicates the need for platforms where families, communities, and schools share information on access and success in public school in the United States. Among other areas, families cite the need for information on the developmental and social needs of K-12 students and resources on immigration, health services, and employment.